Interprofessional teamwork in stroke care: Is it visible or important to patients and carers?. Issue 4 (July 2015) - Hewitt, Gillian; Sims, Sarah; Greenwood, Nan; Jones, Fiona; Ross, Fiona; Harris, Ruth
Abstract Interprofessional teamwork is seen in healthcare policy and practice as a key strategy for providing safe, efficient and holistic healthcare and is an accepted part of evidence-based stroke care. The impact of interprofessional teamwork on patient and carer experience(s) of care is unknown, although some research suggests a relationship might exist. This study aimed to explore patient and carer perceptions of good and poor teamwork and its impact on experiences of care. Critical incident interviews were conducted with 50 patients and 33 carers in acute, inpatient rehabilitation and community phases of care within two UK stroke care pathways. An analytical framework, derived from a realist synthesis of 13 'mechanisms' (processes) of interprofessional teamwork, was used to identify positive and negative 'indicators' of teamwork. Participants identified several mechanisms of teamwork, but it was not a subject most talked about readily. This suggests that interprofessional teamwork is not a concept that is particularly important to stroke patients and carers; they do not readily perceive any impacts of teamwork on their experiences. These findings are a salient reminder that what might be expected by healthcare professionals to be important influences on experience may not be perceived to be so by patients and carers.